Perilaku Politik Orang Banjar di Perbaungan - RIZA, FAISAL (Politeia: Jurnal Ilmu Politik, 2011)
This study focused on Urang Banjar in the Kecamatan (district) Perbaungan Kabupaten Serdang Bedagai Sumatera Utara Province. At this case the Banjar known as Islam. They view that the values of Islam must inheren into multiaspect of human life. Based on this, they political mainstream is integrality between Islam and politic. This study aimed to answer three questions. First, how the Banjar realize their religion believes in politics, as in the general election or the presidential election, and the regional leader? Is loyality to Islamic party as loyality to Islamic figure inside? What the factors influence they political behavior? The result seen that in Urang Banjar view politics and religion are integral. Moreover Urang Banjar tend loyal to Islamic parties, however, loyalty to the partai Islam is not always linear with their loyalty to Islamic figures within the Islamic parties, especially in the context of the Presidential Election and Pemilukada. Finally, this study found that political behavior of the Banjar is influenced by many factors like the religion believe, history, culture, social economic and the Islamic party Performance.Keywords: Political behavior, general election, political participation.